DEGREE OF AWARENESS OF SOFT RELINING MATERIALS BY DENTAL TECHNICIANS - Ilian Hristov; Tanya Boshkova; Stoyan Yankov; Dobromira Shopova; Stefan Zlatev (Peytchinski Publishing, 2017)
The aim of the current investigation is to analyze the dental-technicians' awareness of the soft relining materials, their characteristics, advantages, shortcomings and methods for relining. Materials and methods: For the purpose of this investigation a standard questionnaire has been presented. A direct survey method, documentary and statistical method, as well as graphical methods, including tables, charts, graphics and figures, were used. Data were analysed with the help of IBM SPSS Statistics (ver. 19). Results: One hundred and eight dental technicians were included in the survey, evenly distributed by gender. Removable and fixed prosthodontics is the most commonly mentioned spheres of dental activities. Almost all included in the investigation point out the laboratory relining method as the most frequently used. Acrylic and silicone SRM are the most used groups of relining materials. Change of colour and hardness are the most frequently noticed shortcomings of these materials. The majority of the dental technicians declare that they have never done replacement of SRM or the relining has lasted more than a year. Discussion: The correlation between the age and the years of labour service among the participants is quite obvious. Most of them start working soon after their graduation. Removable prosthodontics is among the priorities for the majority of the labs. Conclusion: Although their unambiguous advantages, the soft relining materials have lots of shortcomings as well. The major problems are connected with their change of colour and hardness. Nevertheless, the dental technicians find them useful and reliable in overcoming specific prosthetic problems.